Manhaj dakwah para nabi dengan landasan hikmah dan rasio Rabi bin Hadi Al Madkhali; penerjemah, Abu Fahmi; penyunting, M.S. Arief - RABI BIN HADI AL MADKHALI; Abu Fahmi; Arief, M.S (Gema Insani Press, 1995)
168 hlm 18 cm